Sodium ion slurry battery, negative electrode slurry and preparation method of negative electrode slurry

By using a specific ratio of negative electrode active materials, conductive agents and electrolytes in sodium ion slurry cells, combined with the stirring and dispersion process of the dual planetary stirred tank, the problems of slurry settlement and poor conductivity are solved, and the slurry is realized Good dispersion and anti-settlement performance improve the cycle stability and electrochemical performance of the battery.

CN119481048APending Publication Date: 2025-02-18ZHENGZHOU ZHONGKE EMERGING IND TECH RES INST +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411809924.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The negative electrode slurry in sodium ion slurry cells has problems of settling and poor conductivity, which affects the conductivity network continuity of the electrode and the battery performance.

Method used

Using the specific ratio of negative electrode active material, conductive agent and electrolyte, a slurry with good dispersion and anti-settlement properties is prepared through the stirring and dispersion process of the dual planetary stirred tank.

Benefits of technology

The prepared slurry has good conductivity and stability, can maintain long-term suspension stability, and improve the cycle stability and electrochemical performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481048A_ABST
    Figure CN119481048A_ABST
Patent Text Reader

Abstract

The invention provides a sodium ion slurry battery, negative electrode slurry and a preparation method of the negative electrode slurry, belongs to the technical field of slurry batteries, and aims to solve the technical problems of sedimentation and poor conductivity of the negative electrode slurry in the sodium ion slurry battery. A conductive agent and a hard carbon material in a certain proportion are mixed to obtain blended dry powder, then a staged mixing method is adopted, the raw materials are preliminarily mixed under a small amount of electrolyte to promote preliminary fusion of all components, then a certain mass of electrolyte is added again, and stirring is performed to enhance the dispersity and uniformity of the slurry. By optimizing the type and content of the conductive agent and the use amount of the electrolyte, the solid content in the slurry is increased while the conductivity of the slurry is ensured, and the dispersity of solid particles in the slurry is improved. The prepared negative electrode slurry is good in dispersity, free of sedimentation after standing for a long time and high in stability, the electrochemical performance of a sodium ion slurry battery can be effectively improved, the service life of the sodium ion slurry battery can be effectively prolonged, and the negative electrode slurry has wide application prospects in the field of large-scale energy storage of the sodium ion slurry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of slurry batteries, and in particular relates to a sodium ion slurry battery. Background Art

[0002] As the global demand for clean energy continues to grow, energy storage technology has become increasingly important in modern society. Batteries, as an efficient energy storage device, are widely used in many fields such as electric vehicles, smart grids, and portable electronic devices. Among various battery technologies, lithium-ion batteries have achieved great success and occupied a dominant market position in the past few decades due to their advantages such as high energy density and long cycle life. However, with the large-scale application of lithium-ion batteries, the scarcity and rising costs of lithium resources have gradually become prominent, which has prompted researchers to actively explore new battery systems to meet the growing demand for energy storage. Sodium-ion batteries, as a potential energy storage solution, have received widespread attention in recent years.

[0003] In addition, combining the advantages of low cost of sodium-ion batteries and high flexibility of flow batteries, sodium-ion slurry batteries are a new type of battery technology with the advantages of low cost, flexible design, independent design, and high energy density, and are expected to be used for large-scale energy storage.

[0004] In the manufacturing technology of sodium-ion slurry batteries, the preparation process of electrode slurry plays a decisive role in the performance of the battery. Sodium-ion slurry batteries are made by mixing active materials, conductive agents and electrolytes to form a slurry, which is directly applied to the battery. No binder is used, and the preparation process does not require processes such as pole piece drying. Unlike the fixed pole piece structure of sodium-ion batteries, in slurry batteries the active materials are directly suspended in the electrolyte, and the active particles are in an unbound state. The interactions between the active materials, conductive agents and electrolyte components in the slurry are complex. After being stored for a period of time, the slurry may have problems such as sedimentation and stratification, which will affect the uniformity and stability of the slurry, and then affect the continuity of the conductive network of the electrode, causing the battery performance to decay. Therefore, sodium-ion slurry electrodes need to have good dispersibility and stability. Summary of the invention

[0005] In view of the technical problems of sedimentation and poor conductivity of negative electrode slurry in sodium ion slurry batteries, the present invention proposes a sodium ion slurry battery, a negative electrode slurry and a preparation method thereof. The slurry prepared by the method has good dispersibility and anti-sedimentation performance, and the slurry is assembled into a sodium ion slurry battery with good electrochemical performance.

[0006] In order to achieve the above object, the technical solution of the present invention is achieved as follows:

[0007] A negative electrode slurry for a sodium ion slurry battery, comprising the following raw materials in the following weight proportions: 5-50% of a negative electrode active material, 0.1-10% of a conductive agent, and 40-90% of an electrolyte

[0008] Furthermore, the negative electrode active material is hard carbon, and the conductive agent is one or a mixture of conductive carbon black, Ketjen black, conductive graphite, carbon nanofiber, carbon nanotube, and graphene.

[0009] Furthermore, the electrolyte includes a non-aqueous organic solvent and a sodium salt. The non-aqueous solvent mainly includes one or more of dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), ethylene carbonate (EC), propylene carbonate (PC), 1,3-dioxolane (DOL), ethylene glycol dimethyl ether (DME), diethylene glycol dimethyl ether (Diglyme) and tetraethylene glycol dimethyl ether (Triglyme).

[0010] Furthermore, the sodium salt is one or more of sodium hexafluorophosphate, sodium perchlorate, sodium trifluoromethanesulfonate, sodium bis(trifluoromethanesulfonyl)imide, sodium bis(trifluoromethanesulfonyl)imide, sodium tetrafluoroborate, and sodium difluorooxalatoborate, and the concentration of the sodium salt is 1-2 mol / L.

[0011] A method for preparing a sodium ion slurry battery comprises the following steps:

[0012] (1) mixing the negative electrode active material and the conductive agent to obtain a premixed dry powder;

[0013] (2) Add the electrolyte to the premixed dry powder, mix, and stir to disperse to obtain the negative electrode slurry.

[0014] In the step (2), the electrolyte is added twice, first adding 40-60wt% of the electrolyte and mixing evenly, and then adding the remaining electrolyte; by preliminarily mixing the raw materials in a small amount of electrolyte to promote the initial fusion of the components, and then adding a certain mass of electrolyte again and stirring, the dispersion and uniformity of the slurry are enhanced.

[0015] The mixing in step (2) is carried out in a double planetary stirring kettle, with a stirring speed of 100 to 6000 rpm, a temperature in the stirring kettle controlled at 20 to 30° C., and a mixing time of 0.1 to 1 h.

[0016] Furthermore, the above preparation method needs to be carried out at an ambient temperature within the range of 20-30°C and a dew point temperature below -50°C.

[0017] A sodium ion slurry battery comprises a positive electrode shell, a sodium sheet, a diaphragm, a negative electrode slurry, a current collector, a gasket, a spring and a negative electrode shell. The electrolyte is a part of the slurry and has been added during the preparation of the slurry, so no additional electrolyte is added during the assembly of the button battery.

[0018] Beneficial effects of the present invention: The present invention prepares a sodium ion slurry battery negative electrode slurry with good conductivity and slurry stability. By adjusting the type and amount of the conductive agent, optimizing the ratio of the solvent and the sodium salt in the electrolyte, and regulating the ratio of the active material, the conductive agent and the electrolyte, a slurry with high stability and continuous and rapid electron / ion transmission efficiency is prepared. The conductive agent can not only serve as a self-repairing current collector, but also prevent the large particles of the active material from sinking through its hyperbranched structure to maintain the stability of the suspension. By optimizing the ratio of the electrolyte, the ion / electronic conductivity of the slurry is effectively improved, and the viscosity of the slurry is reduced, so that the slurry can flow well in the pipeline and the reactor. During use, the problems such as a sharp drop in conductivity and performance attenuation caused by slurry sedimentation, volume change, and electrolyte volatilization can be prevented, which is conducive to promoting the large-scale application of slurry batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 This is the battery slurry prepared from the negative electrode active material in Example 1.

[0021] Figure 2 The scanning electron microscope images of the battery slurry in Example 1, (a) is a low magnification, and (b) is a high magnification.

[0022] Figure 3 The electrochemical performance of the negative electrode slurry prepared in Example 1. DETAILED DESCRIPTION

[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Example 1

[0025] A sodium ion slurry battery negative electrode slurry, the preparation method comprising the following steps:

[0026] (1) The negative electrode active material is hard carbon, the conductive agent is conductive carbon black, and the electrolyte is prepared by dissolving 1.0 mol / L NaPF6 in diethylene glycol dimethyl ether. The negative electrode active material, the conductive agent and the electrolyte are weighed in a mass ratio of 20%:2%:78% and prepared.

[0027] (2) Premixed dry powder: The negative electrode active material hard carbon and the conductive agent conductive carbon black are placed in a stirring tank of a double planetary stirring kettle, stirred at a speed of 600 rpm, dispersed at a speed of 1200 rpm, mixed for 20 minutes, and the process temperature is 20-30°C to obtain a premixed dry powder.

[0028] (3) Primary slurry mixing: Weigh the active material hard carbon, conductive carbon black and half of the total mass of the electrolyte, add them into a stirring tank, put them into a double planetary stirring kettle, stir at 600 rpm, disperse at 1200 rpm, mix for 20 min, and keep the process temperature at 20-30°C to obtain a primary mixture in which the mass ratio of hard carbon to conductive carbon black is 10:1.

[0029] (4) Negative electrode slurry: The remaining electrolyte was added to the primary mixed slurry of step (3), stirred at 600 rpm, dispersed at 1200 rpm, mixed for 20 min, and the process temperature was 20-30° C. to obtain a hard carbon negative electrode slurry. The optical photograph is as follows: Figure 1 shown.

[0030] Figure 2 Scanning electron microscope (SEM) images of hard carbon negative electrode slurry at different magnifications.

[0031] Example 2

[0032] A sodium ion slurry battery negative electrode slurry, the preparation method comprising the following steps:

[0033] (1) The negative electrode active material is hard carbon, the conductive agent is Ketjen black, and the electrolyte is prepared by dissolving 1.0 mol / L NaPF6 in diethylene glycol dimethyl ether. The negative electrode active material, the conductive agent and the electrolyte are weighed in a mass ratio of 20%:2%:78% and prepared.

[0034] (2) Premixed dry powder: The negative electrode active material hard carbon and the conductive agent Ketjen black were placed in a stirring tank of a double planetary stirring kettle, stirred at 600 rpm, dispersed at 1200 rpm, mixed for 20 min, and the process temperature was 20-30°C to obtain a premixed dry powder.

[0035] (3) Primary slurry mixing: Weigh the active material hard carbon, Ketjen black and half of the total mass of the electrolyte, add them into a stirring tank, put them into a double planetary stirring kettle, stir at 600 rpm, disperse at 1200 rpm, mix for 20 min, and the process temperature is 20-30°C to obtain a primary mixture, in which the mass ratio of hard carbon to Ketjen black is 10:1.

[0036] (4) Negative electrode slurry: Add the remaining electrolyte to the primary mixed slurry of step (3), stir at 600 rpm, disperse at 1200 rpm, mix for 20 min, and process at 20-30° C. to obtain hard carbon negative electrode slurry.

[0037] Example 3

[0038] A sodium ion slurry battery negative electrode slurry, the preparation method comprising the following steps:

[0039] (1) The negative electrode active material is hard carbon, the conductive agent is conductive graphite, and the electrolyte is prepared by dissolving 1.0 mol / L NaPF6 in diethylene glycol dimethyl ether. The negative electrode active material, the conductive agent and the electrolyte are weighed in a mass ratio of 20%:2%:78% and prepared.

[0040] (2) Premixed dry powder: The negative electrode active material hard carbon and the conductive agent conductive graphite are placed in a stirring tank of a double planetary stirring kettle, stirred at a speed of 600 rpm, dispersed at a speed of 1200 rpm, mixed for 20 minutes, and the process temperature is 20-30°C to obtain a premixed dry powder.

[0041] (3) Primary slurry mixing: Weigh the active material hard carbon, conductive graphite and half of the total mass of the electrolyte, add them into a stirring tank, put them into a double planetary stirring kettle, stir at 600 rpm, disperse at 1200 rpm, mix for 20 min, and keep the process temperature at 20-30°C to obtain a primary mixture, in which the mass ratio of hard carbon to conductive graphite is 10:1.

[0042] (4) Negative electrode slurry: Add the remaining electrolyte to the primary mixed slurry of step (3), stir at 600 rpm, disperse at 1200 rpm, mix for 20 min, and process at 20-30° C. to obtain hard carbon negative electrode slurry.

[0043] Comparative Example 1

[0044] The difference from Example 1 is that in step (1), the mass ratio of the negative electrode active material, the conductive agent and the electrolyte is 1%:1%:98%.

[0045] Comparative Example 2

[0046] The difference from Example 1 is that in step (1), the mass ratio of the negative electrode active material, the conductive agent and the electrolyte is 4%:1%:95%.

[0047] Comparative Example 3

[0048] The difference from Example 1 is that in step (1), the mass ratio of the negative electrode active material, the conductive agent and the electrolyte is 55%:2%:43%.

[0049] The negative electrode slurry prepared in Example 1 was subjected to slurry stability and electrochemical performance tests, and the negative electrode slurry was placed in a transparent glass bottle for suspension stability test. The obtained slurry had no sedimentation within 10 days and had good fluidity.

[0050] The electrochemical performance of button cells assembled with the slurries prepared in Examples 1-3 and Comparative Examples 1-3 was tested. The preparation process is as follows: Use nickel foam with conductivity and three-dimensional network structure as the carrier of the slurry. When dripping the slurry, drip it on an analytical balance and record the mass. After dripping, assemble the battery in the following order: positive electrode shell, lithium sheet, diaphragm, nickel foam, slurry, negative electrode shell. The test conditions are 0.01V-2V, and the test current is 0.1C. The test results of the negative electrode slurry in Example 1 are as follows: Figure 3 As shown, after 50 cycles, the capacity retention rate is 96.2%.

[0051] Table 1

[0052]

[0053] It can be seen from Table 1 that in Examples 1-3, cycle tests were carried out at a current density of 0.1C, which showed the effect of different conductive agents on the performance of the slurry electrode. When conductive carbon black is used as a conductive agent, the cycle stability of the slurry is significantly improved, and the electrochemical performance is even better. During the cyclic charge and discharge process, the conductive carbon black is evenly dispersed in the slurry system. Due to its own high specific surface area, it builds an efficient and stable conductive path for electron transmission. This allows electrons to move quickly and smoothly between the active material particles during the charge and discharge process, thereby ensuring the stable performance of the overall battery performance.

[0054] It can be seen from Table 1 that, under the premise of keeping the conductive agent unchanged, the ratio of active material to electrolyte is one of the key factors affecting the specific capacity and cycle stability of the slurry. In Comparative Examples 1-3, compared with Example 1, the same conductive agent is selected, but when the ratio of active material to electrolyte is changed, the specific capacity and cycle stability of the slurry also change accordingly. When the content of active material in the slurry is reduced, it is impossible to form an interconnected conductive network inside it, and the utilization rate of active materials is lower, which limits the electrochemical performance. However, when the content of active material in the slurry is too high, it will lead to a sharp increase in viscosity, agglomeration of active materials and other problems, which is not conducive to the performance of the active material.

[0055] Example 4

[0056] A sodium ion slurry battery negative electrode slurry, the preparation method comprising the following steps:

[0057] (1) The negative electrode active material is hard carbon, the conductive agent is conductive graphite, and the electrolyte is prepared by dissolving 1.0 mol / L sodium bis(fluorosulfonyl)imide in ethylene glycol dimethyl ether. The negative electrode active material, the conductive agent and the electrolyte are weighed in a mass ratio of 5%:10%:85% and prepared.

[0058] (2) Premixed dry powder: The negative electrode active material hard carbon and the conductive agent conductive graphite are placed in a stirring tank of a double planetary stirring kettle, stirred at a speed of 600 rpm, dispersed at a speed of 1200 rpm, mixed for 20 minutes, and the process temperature is 20-30°C to obtain a premixed dry powder.

[0059] (3) Primary slurry mixing: Weigh the active material hard carbon, conductive graphite and 40wt% electrolyte with a total mass, add them into a stirring tank, put them into a double planetary stirring kettle, stir at a speed of 100 rpm, disperse at a speed of 1200 rpm, mix for 20 minutes, and the process temperature is 20-30°C to obtain a primary mixture, in which the mass ratio of hard carbon to conductive graphite is 10:1.

[0060] (4) Negative electrode slurry: Add the remaining electrolyte to the primary mixed slurry of step (3), stir at 600 rpm, disperse at 1200 rpm, mix for 20 min, and process at 20-30° C. to obtain hard carbon negative electrode slurry.

[0061] Example 5

[0062] A sodium ion slurry battery negative electrode slurry, the preparation method comprising the following steps:

[0063] (1) The negative electrode active material is hard carbon, the conductive agent is conductive graphite, and the electrolyte is prepared by dissolving 1.5 mol / L sodium trifluoromethanesulfonate in diethylene glycol dimethyl ether. The negative electrode active material, the conductive agent and the electrolyte are weighed in a mass ratio of 40%:10%:50% and prepared.

[0064] (2) Premixed dry powder: The negative electrode active material hard carbon and the conductive agent conductive graphite are placed in a stirring tank of a double planetary stirring kettle, stirred at a speed of 600 rpm, dispersed at a speed of 1200 rpm, mixed for 20 minutes, and the process temperature is 20-30°C to obtain a premixed dry powder.

[0065] (3) Primary slurry mixing: Weigh the active material hard carbon, conductive graphite and 60wt% of the total mass of the electrolyte, add them into a stirring tank, put them into a double planetary stirring kettle, stir at 600rpm, disperse at 1200rpm, mix for 20min, and keep the process temperature at 20-30℃ to obtain a primary mixture, in which the mass ratio of hard carbon to conductive graphite is 10:1.

[0066] (4) Negative electrode slurry: Add the remaining electrolyte to the primary mixed slurry of step (3), stir at 600 rpm, disperse at 1200 rpm, mix for 20 min, and process at 20-30° C. to obtain hard carbon negative electrode slurry.

[0067] Example 6

[0068] A sodium ion slurry battery negative electrode slurry, the preparation method comprising the following steps:

[0069] (1) The negative electrode active material is hard carbon, the conductive agent is conductive graphite, and the electrolyte is prepared by dissolving 2.0 mol / L sodium perchlorate in propylene carbonate. The negative electrode active material, the conductive agent and the electrolyte are weighed in a mass ratio of 9.9%:0.1%:90% and prepared.

[0070] (2) Premixed dry powder: The negative electrode active material hard carbon and the conductive agent conductive graphite are placed in a stirring tank of a double planetary stirring kettle, stirred at a speed of 600 rpm, dispersed at a speed of 1200 rpm, mixed for 20 minutes, and the process temperature is 20-30°C to obtain a premixed dry powder.

[0071] (3) Primary slurry mixing: Weigh the active material hard carbon, conductive graphite and half of the total mass of the electrolyte, add them into a stirring tank, put them into a double planetary stirring kettle, stir at 600 rpm, disperse at 1200 rpm, mix for 20 min, and keep the process temperature at 20-30°C to obtain a primary mixture, in which the mass ratio of hard carbon to conductive graphite is 10:1.

[0072] (4) Negative electrode slurry: Add the remaining electrolyte to the primary mixed slurry of step (3), stir at 600 rpm, disperse at 1200 rpm, mix for 20 min, and process at 20-30° C. to obtain hard carbon negative electrode slurry.

[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A negative electrode slurry for sodium ion slurry battery, characterized in that: The invention comprises the following raw materials in the following mass proportions: 5-50% of negative electrode active material, 0.1-10% of conductive agent and 40-90% of electrolyte.

2. The negative electrode slurry for sodium ion slurry battery according to claim 1, characterized in that: The negative electrode active material is hard carbon.

3. The negative electrode slurry for sodium ion slurry battery according to claim 1, characterized in that: The conductive agent is one or more of conductive carbon black, Ketjen black, conductive graphite, carbon nanofiber, carbon nanotube and graphene.

4. The negative electrode slurry for sodium ion slurry battery according to claim 1, characterized in that: The electrolyte includes a non-aqueous organic solvent and a sodium salt, and the concentration of the sodium salt is 1-2 mol / L.

5. The negative electrode slurry for sodium ion slurry battery according to claim 4, characterized in that: The non-aqueous organic solvent is one or more of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, ethylene carbonate, propylene carbonate, 1,3-dioxolane, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.

6. The negative electrode slurry for sodium ion slurry battery according to claim 5, characterized in that: The sodium salt is one or more of sodium hexafluorophosphate, sodium perchlorate, sodium trifluoromethanesulfonate, sodium bis(trifluoromethanesulfonyl)imide, sodium bis(trifluoromethanesulfonyl)imide, sodium tetrafluoroborate and sodium difluorooxalatoborate.

7. The method for preparing a sodium ion slurry battery according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) mixing the negative electrode active material and the conductive agent to obtain a premixed dry powder; (2) Add the electrolyte to the premixed dry powder, mix, and stir to disperse to obtain the negative electrode slurry.

8. The method for preparing negative electrode slurry for sodium ion slurry battery according to claim 7, characterized in that: The electrolyte in step (2) is added twice, first adding 40-60wt% of the electrolyte and mixing evenly, and then adding the remaining electrolyte; the stirring and dispersing temperature is 20-30°C and the time is 0.1-1h.

9. A sodium ion slurry battery, characterized in that: The negative electrode slurry comprises the negative electrode slurry according to any one of claims 1 to 6.

10. The sodium ion slurry battery according to claim 9, characterized in that: It also includes a positive electrode shell, a sodium sheet, a diaphragm, a current collector, a gasket, a spring and a negative electrode shell which are arranged in sequence.